Fault Diagnosis Method for Rolling Element Bearing by Using Quantum Theory - Li Wei; Zhang Xiao (Jixie chuandong)
In order to overcome the disadvantages of traditional denosing method always reduces useful information while it removes noise,a fault diagnosis method combining quantum superposition and probability statistic applied to rolling element bearing is proposed,which uses the specific expression in quantum theory. This method utilizes Laplace mathematics statistics models to describe the dual-tree complex wavelet transform coefficient distribution of vibration signal. On the basis that the change characteristic of noise and fault information between adjacent scales is studied,then quantum superposition is employed to distinguish fault information from noise in vibration signal. The rolling element bearing signal from transmission system with fault is used to verify the validity of this proposed approach. The results reveal that this method can effectively enhance fault information while it reduces noise,thus it can extract mechanical fault information from intensive background noise.